Legal and Regulatory Challenges for the Proliferation of Small and Light Weapons in Nigeria - Malami, Salisu; Abdullah, Nor Anita; Mohamed Yusoff, Zuryati (School of Social Sciences, USM, 2017)
The Nigerian security challenges can be significantly ascribed to the proliferation of small and light weapons (SALW). It is a universal phenomenon that causes serious security problems ranging from cattle rustling, armed robbery, assassination, kidnapping, militancy and terrorist attacks. It serves as a main source of obliteration of lives and properties. Controlling the proliferation of SALW is in the interest of government and governed. This paper examines the legal and regulatory challenges curtailing the control of proliferation of SALW in Nigeria. It equally explores and identifies gaps and lacuna in the legal and institutional frameworks. For practical steps towards effective control of proliferation of weapons legal and institutional reforms are suggested. These include the review of the Firearms Act 1959 to include far reaching provisions. The Act should provide for the creation of National Commission on SALW. The research paper is valuable to the policy makers, the security agencies and the entire citizens. Keywords: Small arms, light weapons, challenges, proliferation, Nigeria.